A new type of double dispersion system for water control in fossil hydrogen energy development. (12th November 2019) - Liu, Xiaoqiang; Qu, Zhanqing; Ye, Weibao; Wen, Hongbin; Guo, Yongjie; Zhang, Minglong; Guo, Tiankui; Sun, Ying
Abstract: Water cut is generally rising with the increase of water injection during water flooding development of fossil hydrogen energy reservoir. Conventional chemical profile control agents fail to work for a long time because they are easily affected by the temperature and salinity of fossil hydrogen energy reservoir to form crossflow channel. In this paper, a new dual-disperse profile control agent and flooding system (DDS) is proposed, which uses polymers and microspheres to plug polymer crossflow and improve oil recovery in fossil hydrogen energy development. The viscosity, suspension property, thermal stability and microsphere size expansion of the DDS are tested, and the oil displacement performance is evaluated. The results show that the viscosity of polymer solution is not affected by the addition of microspheres, and the DDS system has good suspension and thermal stability. Due to the adsorption of microspheres in polymers, the particle size of microspheres tends to increase with time. But the expansion slows down gradually, which is beneficial to deep migration. In terms of plugging efficiency, the optimum concentration of DDS is 1500 mg/L polymer and 500 mg/L microsphere, and the optimum injection volume is 0.5Pv. Compared with single polymer flooding system, the new dual dispersion system has better washing resistance and enhanced oil recovery in fossil hydrogen energy development. Highlights: A new DDS dual dispersion profile control system is proposed. The physical property of DDS is tested. The oil displacement performance of DDS is evaluated. DDS can increase oil recovery significantly.